A CULTURAL SEMIOTICS STUDY: ETHNOMATHEMATICAL EXPLORATION IN GEOMETRY MATERIALS THROUGH CULTURAL SITE IN ACEH - Shalsabilla Octania Liesandra (Universitas Majalengka, 2022)
This study aims to interpret Rumoh Aceh as one of the historical artifacts through an ethnomathematical approach to the focus of the material, namely geometry in elementary school, and to find out the philosophical meaning behind the architecture and ornaments of Rumoh Aceh through a cultural semiotic review which was a type of semiotics from the qualitative content analysis method devoted to the semiotic study in certain cultures. This study referred to secondary sources in journal articles, book and document retrieval through relevant websites to a cultural site in Aceh. Furthermore, the primary sources were obtained from observations about Rumoh Aceh and traditional leaders in Aceh during the archipelago module activities. Determination of the data validity from this study was done by triangulation of sources utilizing cross-check. The results of this study reported that several ethnomathematical concepts in the Rumoh Aceh building could be taught in geometry material in elementary school, including; (1) the concept of the position of an angle concerning a line, (2) the concept of a plane figure (square), (3) the concept of a plane figure (rectangle), (4) the concept of a plane figure (a right triangle) and the Pythagorean principle, (5) the concept of a plane figure (isosceles triangle), (6) the concept of a plane figure (trapezoid), (7) the concept of a flat rhombus, (8) the concept of a spatial figure (tube), and (9) the concept of reflection, tessellation, and translation which might be required to be taught on the introduction of basic concepts at the elementary school level (high grade).